INNOVATIVE ACTIVITY IN MODERN EDUCATION: PEDAGOGICAL TECHNOLOGIES AND FACTORS OF PROFESSIONAL COMPETENCE (World Bulletin of Education and Learning, 2025)
This article explores the content of innovative activities in the modern educational system, the principles of its organization and the theoretical and practical aspects of the application of pedagogical technologies. The study evaluated the professional competence of the teacher as a key factor in the innovative pedagogical process, analyzed the possibilities of developing cognitive activity, independent thinking skills and creativity of students through the integration of innovative technologies into the educational process. Also, the methodological infrastructure, motivational-psychological conditions and professional development strategies of teachers are considered, which are necessary for the effective implementation of innovative activities. The results of the article include scientific and practical recommendations aimed at improving innovative approaches in modern education and improving the quality of the pedagogical process.
Keywords: Innovative activity, pedagogical innovation, educational system, teacher competence, interactive methods, digital education, pedagogical technologies, creativity, quality of Education.